2008
DOI: 10.1038/jp.2008.124
|View full text |Cite
|
Sign up to set email alerts
|

Growth in preterm infants fed either a partially hydrolyzed whey or an intact casein/whey preterm infant formula

Abstract: Objective: To compare feeding tolerance, nutrient intake and growth in preterm infants (p32 weeks, p1750 g) fed either a standard nonhydrolyzed whey-casein (nHWC) or a partially hydrolyzed whey (pHW) preterm infant formula.Study Design: In this double-blind randomized controlled trial infants were fed either formula for at least 3 weeks. Intake was monitored daily, serum chemistries and growth weekly. Data were analyzed using analysis of covariance.Result: A total of 80 infants were enrolled, 72 completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 18 publications
4
23
0
Order By: Relevance
“…However a recent study did not find any advantage of hydrolysed over whole-protein formula33 or breast milk34 and a review of the literature up to august 2006 concluded that there was insufficient evidence to warrant routine use of these feeds for preterm infants 35…”
Section: Types Of Feedmentioning
confidence: 99%
“…However a recent study did not find any advantage of hydrolysed over whole-protein formula33 or breast milk34 and a review of the literature up to august 2006 concluded that there was insufficient evidence to warrant routine use of these feeds for preterm infants 35…”
Section: Types Of Feedmentioning
confidence: 99%
“…Other product specifications, including desirable clinical requirements and product features, were considered. Literature was reviewed to identify current evidence for each desirable clinical requirement considered . A weighing system was developed based on clinical experience, with other product specifications contributing a possible 20% of the total score.…”
Section: Methodsmentioning
confidence: 99%
“…To examine this issue, Florendo et al 58 weighed two groups of VLBWI on Day 1. Then assuming a weight gain of 25 g/day, prescribed a ‘target’ intake of 120 kcal/kg/day for the subsequent 4 days.…”
Section: Individualised Nutritional Care/monitoringmentioning
confidence: 99%